2016
DOI: 10.1111/ane.12671
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol withdrawal syndrome: mechanisms, manifestations, and management

Abstract: The alcohol withdrawal syndrome is a well‐known condition occurring after intentional or unintentional abrupt cessation of heavy/constant drinking in patients suffering from alcohol use disorders (AUDs). AUDs are common in neurological departments with patients admitted for coma, epileptic seizures, dementia, polyneuropathy, and gait disturbances. Nonetheless, diagnosis and treatment are often delayed until dramatic symptoms occur. The purpose of this review is to increase the awareness of the early clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(169 citation statements)
references
References 95 publications
2
129
0
13
Order By: Relevance
“…The mechanism behind the alcohol withdrawal seizure might also be strongly linked to sleeplessness, pointing to the importance of the therapeutic effect of sleep induction in the alcohol withdrawal syndrome (Jesse et al, 2016). Moreover, the notion that sleep loss by itself can facilitate the development of seizures is supported by a previous study on the weekday distribution of seizures in relation to alcohol consumption.…”
Section: Sleep and Alcoholmentioning
confidence: 90%
See 3 more Smart Citations
“…The mechanism behind the alcohol withdrawal seizure might also be strongly linked to sleeplessness, pointing to the importance of the therapeutic effect of sleep induction in the alcohol withdrawal syndrome (Jesse et al, 2016). Moreover, the notion that sleep loss by itself can facilitate the development of seizures is supported by a previous study on the weekday distribution of seizures in relation to alcohol consumption.…”
Section: Sleep and Alcoholmentioning
confidence: 90%
“…The pathophysiological mechanisms of alcohol induced seizures are not yet fully understood as the effect of alcohol on the central nervous system is complex, and affect several systems of neurotransmitters, most notably the GABA-/ and glutamate systems (Faingold et al, 1998, Jesse et al, 2016. In patients with a first-time seizure, alcohol appeared to be a contributing factor in more than 30% of admissions (Bråthen et al, 1999).…”
Section: Sleep Alcohol Stress Anxiety Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…To prevent progression to a more severe withdrawal, benzodiazepine is recommended to be used early in the management of alcohol withdrawal [17]. Despite the fact that within the first 2 days of withdrawal, benzodiazepine reduces the incidence of seizures by up to 84% and prevent the development of delirium tremens [9], a previous study found that only 37% of patients with AUD were prescribed with benzodiazepine for alcohol withdrawal management [30].…”
Section: Introductionmentioning
confidence: 99%